Perencanaan Strategis Sistem Informasi pada PT. Indah Kiat Pulp & Paper Tbk - Rainer Hannesto (Bina Nusantara University, 2014)
Business growth nowadays is very rapid. Most organization in all industry depends on information technology to compete in industrial competition. Before make a decision to invest in information technology, better to make planning for alignment between information technology and strategy that can brings benefit to company. The lack of information System strategic planning can have an impact on the achievement of the vision and mission of the organization.This research was conducted based on the framework by Ward & Peppard. Researchers interviewed the management and doing direct observation to determine the current business processes. Researchers also get the data by distributing questionnaires to the employees of the organization as well as literature. The result of this study is the composition of an application portfolio that contains information system strategic planning needs, management and infrastructure also performance measurement targets indication based on the results of the analysis of the Balanced Scorecard.